Effect of Graphene Oxide on the Characteristics of sPEEK-Chitosan Membranes for Direct Methanol Fuel Cells - Herry Purnama; Indra Viki Hartoko; Muhammad Mujiburohman; Nur Hidayati (Automotive Experiences, 2020)
Direct Methanol Fuel Cell (DMFC) can operate at low temperatures, but efficiency and performance are greatly influenced by the material. On the other hand, sulfonated ketone polyether ethers (sPEEK) which have high thermal resistance, ductile, chemical resistance and high mechanical properties, can be combined with chitosan which has good proton conductivity properties. The sPEEK-Chitosan membrane is known to have good mechanical and thermal resistance, but its conductivity is low. The addition of graphene oxide as a filler material can increase the proton conductivity due to its properties. This research was conducted with a completely randomized design of 1 factor to investigate the characteristics of the sPEEK-Chitosan composite membrane as the dependent variable and the addition of graphene oxide solution to the variables 0, 1, 3, 6, and 9% w/w as independent variables. The test results show that the water uptake is in the range of 8.82-33.34%, the swelling degree is in the range of 5.55-20.75%, and the ion exchange capacity is 0.1875-0.2714 meq/g. With this good character, the sPEEK-chitosan membrane with the addition of graphene oxide is a promising candidate for DMFC applications.